Anthelmintic resistance in equine helminths and mitigating its effects. Issue 10 (10th November 2016) - Tzelos, Thomas; Matthews, Jacqueline
Abstract : Helminth control in horses has been based on the administration of broad‐spectrum anthelmintics for over 50 years, but although this has reduced clinical disease, anthelmintic‐resistant populations of nematodes (for example, cyathostomins and Parascaris equorum ) have developed due to frequent 'blanket' treatments. Resistance to benzimidazole, pyrantel and, more recently, macrocyclic lactones is not uncommon so strategies that balance the use of anthelmintics for parasite control with the need to limit selection pressure for resistance should be adopted. An inability to control burdens of these nematodes could cause serious health problems, particularly in younger horses, as well as in the small number of individuals that have a higher susceptibility to high levels of infection throughout life. This article reviews anthelmintic resistance in equine nematodes and the measures that can be taken in practice to try to mitigate its spread.